Influence of Travel Motivation and Demographic Factors on Tourist Participation in World's Largest Mass Religious Gathering - The Kumbh Mela - Verma, Meghna; Verma, Ashish; Khurana, Sagar (Prabandhan: Indian Journal of Management, 2018)
Worldwide, new trends are emerging in tourism, for example, medial tourism, eco tourism, religious tourism, etc. Though destination tourism has gained enormous attention of the academicians, but few studies have been done in context of religious tourism, out of which there are hardly any studies done in the Indian context that explored the motivation of pilgrims or tourists who visit Kumbh Mela. This paper estimated the relationship between demographic factors and travel motivation towards the world's largest mass religious gathering - The Kumbh Mela. An ordered logit model was used to determine the demographic factors which affected visitors' motivation to participate in Kumbh Mela, which was held during April 22, 2016 and May 21, 2016 at Ujjain, Madhya Pradesh, India. A total of 18 models were computed for different motivations of travel. The results suggested that motivations changed within different groups of varying socioeconomic characteristics. Overall, the demographic factors like age, gender, family member, education, income, and psychographic factors like satisfaction with life and life rewarding came out to be statistically significant, while factors like single, unmarried, student, government employee, and private employee came out to be statistically insignificant. This study also computed the overall rankings of the motivations. The outcomes of this study can potentially aid the organizers of such mass religious gatherings for better planning and management of such mega events.